PERANCANGAN SISTEM INFORMASI PROMOSI DAN TRANSAKSI BUKU BERORIENTASI OBJEK PADA PT`. FAJAR AGUNG INDOCEMERLANG - Saleh, Sushanty; Basri, Hasan (Jurnal Informatika, 2012)
PT. Fajar Agung Indocemerlang is one of company that moved in selling various types of books, stationery and also other office equipment. Promotion process is done by distributing pamphlets, brochures and advertisements in newspapers; meanwhile selling is done by customer come to the shop immediately. In this research, design of information system is developed by using object oriented, that is development tools is used use case and activity diagram that describe system for this time and proposed system. Result of design information system is expected to be implemented in web form which design was given from this research include proposed design system, analysis requirement for hardware, software and cost analysis.Keyword: promotion, object oriented, transaction, design system